Percival Everett’s creativity in the context of contemporary american literature - Olga B. Karasik, Inna V. Shchepacheva,; Stulov, Yuri V. (Opción, 2019)
The article deals with the literary creativity of Percival Everett who is considered to be one of the most accomplished and prolific American writers nowadays via comparative qualitative research methods. As a result, the main peculiarity of Percival Everett’s novels is that the author presents his own vision of American and African American literatures and this way of interpretation is based on postmodernist aesthetics mostly. In conclusion, the creativity of Percival Everett is diverse and it presents itself a combination of new and traditional approaches to the themes of American and African American literatures.